Analisis Pembiayaan Pendidikan di SMP An-Naja Boarding School - Ulul Azmi; Maftuhah Maftuhah; Sita Ratnaningsih; Nurochim nurohim; Zahruddin Zahruddin (JIEM (Journal of Islamic Education Management), 2023)
Education financing is a very important component in the process of providing education. Funding is funding issued either by individual students or members of the public, as well as the government for the smooth running of education and the use and use of financing effectively and efficiently. This study aims to describe the financing of education in junior high schoolsAn Naja Boarding School which includes educational funding sources as well utilization and use of the financing. As for approach and the method in this study uses descriptive qualitative data from interviews, observations, and document studies. Data analysis techniques were carried out using qualitative analysis techniques which included data collection, data reduction, data presentation, and drawing conclusions. While the data validity technique, researchers used data and method triangulation techniques. The results of the study show that the financing system for SMP An Naja Boarding School is centralized, centered on the foundation. schools offer educational fees that are affordable to education customers, and are lower when compared to private educational institutions in the area. Educational resources and use include: students, BOS funds, regular regional donors, incidental grants, waqf and grants, and activity proposals. Sources of education costs are allocated to all the needs of schools and also Islamic boarding schools. The analysis of educational costs produces investment costs, operational costs, and educational personal costs.Keywords: Education Financing, Effectiveness Cost Analysis